2014
DOI: 10.2478/raon-2013-0057
|View full text |Cite
|
Sign up to set email alerts
|

Oral cavity and oropharyngeal squamous cell carcinoma in young adults: a review of the literature

Abstract: BackgroundHead and neck squamous cell carcinoma (HNSCC) is a disease of middle-aged to elderly adults. However, an increased incidence of HNSCC in young people under 45 years of age has been reported recently. In the present review, we focused on the epidemiology and aetiology of HNSCC in adults under 45 years of age.MethodsWe reviewed literature related to HNSCC in adult patients less than 45 years of age and discussed current treatment options and prognosis.ResultsHNSCC in young adults is associated with a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
110
0
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(135 citation statements)
references
References 74 publications
5
110
0
7
Order By: Relevance
“…14 However, Majchrzak et al 15 suggested that there will be an increase in OSCC incidence in young adults in the coming years. The development of this malignancy was observed mainly in females, and can be explained by the recent involvement of women in risky health practices.…”
Section: Discussionmentioning
confidence: 99%
“…14 However, Majchrzak et al 15 suggested that there will be an increase in OSCC incidence in young adults in the coming years. The development of this malignancy was observed mainly in females, and can be explained by the recent involvement of women in risky health practices.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of metachronous and/or synchronous MN was defined according to the international association of cancer registry rules [32]. EO of cancer was defined for each primary tumor as follows: for NSCLC ≤60 years [33], for kidney cancer ≤46 years [34], for urothelial cancer ≤40 years [35][36][37], for melanoma ≤39 years [38,39], for colorectal cancer <50 years [40] and <45 years for head and neck carcinomas [41]. renal cell carcinoma 41 patients (19.4%), melanoma 51 patients (24.2%), NSCLC 104 patients (49.3%), urothelial cancer 10 patients (4.7%), colorectal cancer three patients (1.4%) and head and neck carcinomas two patients (1%).…”
Section: Definition Of Family History Of Cancer Multiple Neoplasms Andmentioning
confidence: 99%
“…In today's time there are 4% to 13% of the cases of oral squamous cell carcinoma that affects subjects younger than 45 years of age. [4][5][6][7][8][9][10] The most frequently affected site is tongue and it is seen generally amongst alcohol and tobacco users. 4,5 Squamous cell carcinoma of lower lip is generally seen amongst subjects with exposure to sunlight.…”
Section: Introductionmentioning
confidence: 99%